Early Enteral Stressors in Newborns Increase Inflammatory Cytokine Expression in a Neonatal Necrotizing Enterocolitis Rat Model - Rentea, Rebecca Maria; Welak, Scott R.; Fredrich, Katherine; Donohoe, Deborah; Pritchard, Kirkwood A.; Oldham, Keith T.; Gourlay, David M.; Liedel, Jennifer L. (European Journal of Pediatric Surgery, 2013)
Introduction Inflammation in the premature intestine is a key factor that leads to the development of necrotizing enterocolitis (NEC). Activation of nuclear factor kappa B (NF-κB) and subsequent inflammation increases the severity of NEC. The aim of this study was to investigate the early temporal expression of inflammatory markers and activation of NF-κB in a neonatal rat model of NEC.Methods Pre- and full-term newborn Sprague-Dawley rat pups were sacrificed at birth, 1.5, 4, 8, and 24 hours after receiving their first feed. Control pups were vaginally delivered and mother fed; NEC was induced by a combination of gavage feeding formula, hypoxia, and enteral lipopolysaccharide (LPS); and formula fed pups were fed every 4 hours with infant formula. Ileal tissue was collected for immunohistochemistry, real-time polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay. Serum was collected for cytokine content. Fold change of expression of inducible nitric oxide synthase (iNOS), interleukin (IL)-1β, IL-6, tumor necrosis factor-α (TNF-α), IL-10, NF-κB p65, and IκBα used RT-PCR. Data were analyzed by paired two-tailed t test, expressed as mean ± standard error of the mean, and p ≤ 0.05 considered significant.Results No histologic injury was evident in ileal sections. At 1.5 h, iNOS expression increased twofold over control in NEC pups (2.1 vs. 1.0, p ≤ 0.05) and remained elevated at 24 h (0.7 vs. 9.4, p ≤ 0.05). IL-1β and IL-6 reached a peak at 24 h in NEC tissue compared with control. IL-10 expression rose in NEC pups after 4 h of insult and remained elevated in formula and NEC stressed pups. Coincident with an increase in p65 translocation into the nucleus and a reduction of IκBα detected in the cytoplasm, increased transcription of IκBα occurs.Conclusion These findings suggest that NF-κB activation initiates inflammation early in the course of NEC resulting in increased proinflammatory protein expression, underscoring the importance of the inflammatory response in this NEC model, which precedes evidence of histological injury.
Keywords: necrotizing enterocolitis (NEC); cytokine; inflammation; NF-kB; formula